Factors associated with type 2 diabetes mellitus treatment choice across four European countries - Heintjes, E; Overbeek, J; Hall, G; Prieto-Alhambra, D; Lapi, F; Hammar, N; Bezemer, I (Elsevier, 2017)
Purpose: To identify factors associated with the choice of type 2 diabetes mellitus (T2DM) therapy at the time of intensification of antidiabetic treatment across four European countries. Methods: For T2DM patients from the Netherlands (NL), Italy (IT), Spain (ES) (2007-2011) and United Kingdom (UK) (2008-2012) antidiabetic drug prescription/dispensing records and patient characteristics were obtained from electronic health-care records. Oral monotherapy was defined as 1st line, oral dual therapy as 2nd line, >2 oral treatments or oral combined with an injectable as 3rd line and injectables only as 4th line treatment. Treatment intensification was defined as starting a higher line of treatment. Comedication, comorbidities, clinical parameters and other factors associated with treatment choice were identified using multivariable relative risk estimation by Poisson regression with robust error variance. Findings: In the study period 485,120 patients, i.e. 79% of the treated T2DM population underwent treatment intensification. Changes in treatment choice were clearly visible over the study period, such as decline of thiazolidinedione (TZD) use (NL, ES, UK), and increase of dipeptidyl peptidase-4 inhibitors (DPP4i) use (NL, ES, UK) and glucagon-like peptide-1 receptor agonist (GLP-1ra) use (UK). For 1st line treatment advanced age and renal comorbidity were associated with SU (all countries), whereas high BMI was inversely associated with SU in UK and ES. For 2nd line advanced age was associated with metformin + SU (all countries) and renal comorbidity with SU + dipeptidyl peptidase-4 inhibitors (DPP4i) in UK and NL. High BMI was associated with metformin + thiazolidinedione (TZD) in UK and ES, and with metformin + DPP4i (UK). For 3rd line advanced age and renal comorbidity were associated with SU + insulin (NL, ES, UK). HbA1c ≥8.5% was positively and high BMI inversely associated with any 3rd line combination containing insulin. For 4th line treatment women were more likely to receive GLP-1ra than men in UK and ES. Implications: The results suggest that the main factors driving treatment choice at any stage of intensification were age, HbA1c, BMI, renal and cardiac morbidity, and prior treatment history. These drivers were consistent with guidelines and contra-indications for specific medications. Differences between countries were generally consistent with, but not solely attributable to differences in local guidelines and reimbursement policies.